2018
DOI: 10.1016/j.radonc.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Standard whole prostate gland radiotherapy with and without lesion boost in prostate cancer: Toxicity in the FLAME randomized controlled trial

Abstract: In intermediate- and high-risk prostate cancer patients, focal dose escalation integrated with standard EBRT did not result in an increase in GU and GI toxicity when compared to the standard treatment up to two years after treatment. This suggests that the described focal dose escalation technique is safe and feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 24 publications
0
76
1
Order By: Relevance
“…Intermediateand high-risk PCa patients were randomised into the standard arm that delivered 77 Gy to the whole gland over 35 fractions or the experimental arm that received a focal boost to the DIL resulting in a total dose of 95 Gy. Focal dose escalation demonstrated comparable genitourinary (GU) and gastrointestinal (GI) toxicity to the standard arm up to two years post-treatment [15]. Murray et al recently reported on preliminary results from the DELINEATE trial that applied focal dose escalation to conventionally-fractionated and hypofractionated IMRT for intermediate-and high-risk PCa [16].…”
Section: Image-guided Focal Dose Escalation In Pca Imrtmentioning
confidence: 99%
“…Intermediateand high-risk PCa patients were randomised into the standard arm that delivered 77 Gy to the whole gland over 35 fractions or the experimental arm that received a focal boost to the DIL resulting in a total dose of 95 Gy. Focal dose escalation demonstrated comparable genitourinary (GU) and gastrointestinal (GI) toxicity to the standard arm up to two years post-treatment [15]. Murray et al recently reported on preliminary results from the DELINEATE trial that applied focal dose escalation to conventionally-fractionated and hypofractionated IMRT for intermediate-and high-risk PCa [16].…”
Section: Image-guided Focal Dose Escalation In Pca Imrtmentioning
confidence: 99%
“…Dose escalation on intraprostatic GTV was feasible in 14/15 patients and with a median follow-up of 18 months no patient developed gastrointestinal/genitourinary toxicities ≥3. Recently, a randomized, multicenter Phase III study (FLAME trial) reported toxicity outcomes after a median follow-up of 55 month in 571 patients [83]. The standard treatment arm received a dose to the entire prostate of 77 Gy in 35 fractions.…”
Section: Mpmrimentioning
confidence: 99%
“…Due to the last decade of research into standard fractionation we have also developed alternative methods of tipping the therapeutic ratio in our favour, such as increasing dose solely to the dominant tumour lesion seen on magnetic resonance imaging at diagnosis, rather than to the whole gland. The concept of a biological target volume, dose-escalated focally to improve PSA control rates [14], has been tested in the FLAME [15] and DELINEATE [16] trials. These trials, and others [17], suggest that focal boosting can be achieved with little/no penalty to toxicity; it remains to be seen whether focal boosting increases control or cure rates.…”
Section: Introductionmentioning
confidence: 99%